Effects of language background on executive function: Transfer across task and modality - Kim, Yeonwoo; Ye, Zixuan; Leventhal, Zachary; Wang, Wei-Ju; Thiessen, Erik D. (Frontiers in Psychology, 2023)
The relation between linguistic experience and cognitive function has been of great interest, but recent investigations of this question have produced widely disparate results, ranging from proposals for a “bilingual advantage”, to a “bilingual disadvantage”, to claims of no difference at all as a function of language. There are many possible sources for this lack of consensus, including the heterogeneity of bilingual populations, and the choice of different tasks and implementations across labs. We propose that another reason for this inconsistency is the task demands of transferring from linguistic experience to laboratory tasks can differ greatly as the task is modified. In this study, we show that task modality (visual, audio, and orthographic) can yield different patterns of performance between monolingual and multilingual participants. The very same task can show similarities or differences in performance, as a function of modality. In turn, this may be explained by the distance of transfer – how close (or far) the laboratory task is to the day to day lived experience of language usage. We suggest that embodiment may provide a useful framework for thinking about task transfer by helping to define the processes of linguistic production and comprehension in ways that are easily connected to task manipulations.